A model for the study of African music - Omibiyi, Mosunmola (International Library of African Music, 1973)
In recent years, African music which some in the past had considered as 'grotesque', 'cacophonous', and a perversion of the norm in music has gained wide acceptance and respectability. Its formal study in a number of institutions in Euro-America, combined with research into its various forms, is becoming increasingly popular. Thus, it is not uncommon to find elementary and high school children learning African songs and dances in their original languages and at the college level, apart from full-time scholarship, students are given experiences in performing African music either through singing of songs, dancing or playing of various musical instruments
Keywords: African Music